Akulturasi Budaya Islam dalam Tradisi Saeyyang Pattuqduq di Desa Karama Kecamatan Tinambung Kabupaten Polewali Mandar - Junaedi (Lentera Jurnal, 2025)
This research uses a qualitative approach with field research, integrating historical, anthropological, and religious approaches. The sources of data for this research involved the Karama Village Head, Karama Village culturists, Karama Village religious leaders, and Karama Village Village Head. The data collection methods include observation, interviews, photovoice, and documentation. The data analysis was carried out through three stages: data reduction, data display, and conclusion drawing. The results showed that acculturation in the Saeyyang Pattuqduq tradition involves elements of local culture such as Mandarese language, music, and traditional clothing influenced by Islamic teachings. This process occurs through an inclusive cultural approach, fostering unity and harmony, and respect for customs, which preachers and ulama carry out in harmonising local cultural elements with Islamic teachings. Islamization is evident in the changes in prayer readings, ritual implementation, and the orientation of the purpose of the activity, which was originally magical, turning into a thanksgiving ritual based on faith in Allah SWT. The implications of this research are expected to provide insight into the form of acculturation in the Saeyyang Pattuqduq tradition in Karama Village, as well as enrich understanding of the dynamics of the relationship between local culture and Islam in the local community.